2015
DOI: 10.1021/bi501252z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Ala81His Mutation on the Met80 Loop Dynamics of Iso-1-cytochromec

Abstract: An A81H variant of yeast iso-1-cytochrome c is prepared to test the hypothesis that the steric size of the amino acid at sequence position 81 of cytochrome c, which has evolved from Ala in yeast to Ile in mammals, slows the dynamics of the opening of the heme crevice. The A81H mutation is used both to increase steric size and to provide a probe of the dynamics of the heme crevice through measurement of the thermodynamics and kinetics of the His81-mediated alkaline conformational transition of A81H iso-1-cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 84 publications
(331 reference statements)
2
26
0
Order By: Relevance
“…Thus, Cyt c can oxidize the lipids such as cardiolipin on the mitochondrial membrane to enhance the membrane permeability, which promotes the release of Cyt c to the cytoplasm and subsequently facilitates the assembly of the apoptosome. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, Cyt c can oxidize the lipids such as cardiolipin on the mitochondrial membrane to enhance the membrane permeability, which promotes the release of Cyt c to the cytoplasm and subsequently facilitates the assembly of the apoptosome. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…The peroxidase activity of Cyt c is linked to loss of the Met80-heme bond [5, 6]. Thus, there has been considerable interest recently in the factors that control the stability of the heme crevice [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that Tyr67 plays a crucial role in maintaining this structure in human cyt c [14]. However, although the amino acid sequence of human and yeast cyt c share about 70% identity [10], major differences between these two cytochromes are found for the surface amino acid residues involved in cardiolipin binding and modulation of the peroxidase activity [23]. Therefore, caution must be used when comparing conformational stability and peroxidase activity between various cyt c proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The release of cyt c from mitochondria into the cytosol upon CL peroxidation is an important apoptotic trigger [7,8]. The identification of these alternative conformations and characterization of the structural features that determine the flexibility of the cyt c-CL complex, which confer to the protein important roles in "life" and "death" processes, continue to be a major challenge [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation